Theoretical evidence for empirical findings of A. Pulgarin on Lotka’s law - L., Egghe (Malaysian Journal of Library and Information Science, 2012)
In [A. Pulgarin. 2012. Dependence of Lotka’s law parameters on the scientific area. Malaysian Journal of Library and Information Science, 17(1): 41-50], the author finds negative correlations between the average number of papers per author and the Lotka exponent and the Lotka constant as well as positive correlations between the latter two parameters. He also finds lower values for the latter two parameters in fields or countries with highly concentrated productions (e.g. where there is heavy growth). In the present paper these findings are proved mathematically, based on earlier results on Lotka’s law proved by this author.